Composite solid electrolyte membrane and preparation method thereof, solid lithium metal battery
Patent Information
- Application Number
- CN202510510011.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-22
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]本申请的目的在于提供一种复合固态电解质膜及其制备方法、固态锂金属电池,旨在解决如何更好地提高固态锂金属电池的电化学性能的问题
[0025]本申请第一方面提供的复合固态电解质膜中,聚合物多孔膜位于固态电解质层内部被其包裹,聚合物多孔膜可以提供较强的力学性能,从而为复合固态电解质膜起到很好的支撑作用,而固态电解质层表面嵌入的锂颗粒不仅可以作为填料增强固态电解质,而且可以提高极限电流密度。因此,本申请提供的复合固态电解质膜用于固态电池中可以很好地降低负极枝晶生长风险,同时提高电池倍率性能,使电池具有很好循环充放电性能。
Smart Images

Figure CN122968420A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of solid-state battery technology, and particularly relates to a composite solid-state electrolyte membrane and its preparation method, and a solid-state lithium metal battery. Background Technology
[0002] Lithium-ion batteries are widely used in electronic devices and electric vehicles; however, currently used lithium-ion batteries struggle to simultaneously meet the requirements of high safety and high energy density. Lithium metal batteries are a type of battery that uses a lithium metal anode instead of the graphite anode in traditional lithium-ion batteries. This is because lithium metal has a high specific capacity (approximately 3860 mAh·g). -1 ), is graphite (372mAh·g -1 Lithium metal batteries are considered to have a wide range of applications, with energy densities more than 10 times higher than those of lithium metal anodes. This means that using lithium metal as an anode can significantly improve battery energy density. However, lithium metal is highly reactive and prone to side reactions with liquid electrolytes, producing gases that can pose safety hazards. Furthermore, directly using lithium metal as an anode can lead to lithium dendrite growth during battery operation, which can penetrate the separator and cause short circuits, resulting in significant heat dissipation and potential fires. Therefore, developing an electrolyte material that is compatible with lithium metal anodes and can resist lithium dendrite penetration is crucial for the development of lithium metal batteries.
[0003] Compared to lithium-ion batteries using liquid electrolytes, using solid-state materials as electrolytes can reduce problems such as electrolyte combustion caused by short circuits. Among the various solid-state electrolytes, polymer solid-state electrolytes are considered to have great commercial potential due to their ease of processing and good compatibility with the negative electrode interface. However, due to their low conductivity, polymer solid-state electrolytes are prone to excessive polarization and lithium dendrite growth. Furthermore, their poor mechanical properties make them less resistant to dendrite penetration, thus easily leading to short circuits. Traditional modification methods involve adding inorganic fillers (such as alumina, lithium lanthanum zirconium oxide, etc.) to increase mechanical properties and conductivity, thereby improving resistance to lithium dendrite growth and penetration into the solid-state electrolyte. However, solid-state electrolytes designed using such methods are often quite thick (e.g., up to 50 μm or more) and can only withstand a low limiting current density, thus reducing the overall volumetric energy density and rate performance of the battery. Summary of the Invention
[0004] The purpose of this application is to provide a composite solid electrolyte membrane and its preparation method, as well as a solid lithium metal battery, aiming to solve the problem of how to better improve the electrochemical performance of solid lithium metal batteries.
[0005] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows:
[0006] In a first aspect, this application provides a composite solid electrolyte membrane, comprising: a polymer porous membrane and a solid electrolyte layer, wherein the solid electrolyte layer covers the polymer porous membrane and is partially embedded in the internal pores of the polymer porous membrane, and the material of the solid electrolyte layer comprises a polymer solid electrolyte; the solid electrolyte layer includes two surfaces disposed opposite to each other, and at least one surface has lithium particles embedded therein.
[0007] In some embodiments, the lithium particles comprise inactive lithium fillers embedded via battery electrochemical deposition-stripping.
[0008] And / or, the lithium particles have a particle size of 50 nm to 10 μm.
[0009] In some embodiments, the polymer solid electrolyte is composed of a polymer and a lithium salt, wherein the polymer is selected from at least one of polyethylene oxide, polyacrylonitrile, and polyvinylidene fluoride, and the lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, and lithium aluminum titanium phosphate.
[0010] In some embodiments, the polymer is selected from polyethylene oxide, the lithium salt is selected from lithium bis(trifluoromethanesulfonyl)imide, and the molar ratio of the polymer to the lithium salt is (14-24):1.
[0011] In some embodiments, the polymer porous membrane is selected from at least one of polyethylene porous membrane, polypropylene porous membrane, polyimide porous membrane, and polyacrylonitrile porous membrane;
[0012] And / or, the polymer porous membrane has a thickness of 2–10 μm, a pore size of 20–300 nm, and a porosity of 30–70%;
[0013] And / or, the thickness of the composite solid electrolyte membrane is less than 20 μm.
[0014] Secondly, this application provides a method for preparing a composite solid electrolyte membrane, comprising the following steps:
[0015] Prepare an electrolyte slurry containing polymers and lithium salts;
[0016] The electrolyte slurry and the polymer porous membrane are mixed and then dried to obtain an initial composite solid electrolyte membrane.
[0017] The initial composite solid electrolyte membrane is assembled with lithium metal into a battery, and then charged and discharged to embed inactive lithium in the surface layer of the initial composite solid electrolyte membrane, thus obtaining a composite solid electrolyte membrane.
[0018] In some embodiments, the molar ratio of the polymer to the lithium salt in the electrolyte slurry is (14–24):1, and the total mass concentration of the polymer and the lithium salt is 0.01–0.1 g·L⁻¹. -1 ;
[0019] And / or, the polymer is selected from at least one of polyethylene oxide, polyacrylonitrile, and polyvinylidene fluoride, and the lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, and lithium aluminum titanium phosphate.
[0020] In some embodiments, the step of mixing the electrolyte slurry and the polymer porous membrane includes: coating the electrolyte slurry on both surfaces of the polymer porous membrane, or placing the polymer porous membrane in the electrolyte slurry and allowing it to stand for 4 to 6 hours;
[0021] And / or, the conditions for the charge-discharge treatment include: 0.2–0.7 mA·cm⁻¹ -2 Under constant current density conditions, charge and discharge cycles were performed for 20–200 hours.
[0022] Thirdly, this application provides a solid-state lithium metal battery, including a positive electrode, a negative electrode, and an electrolyte membrane located between the positive electrode and the negative electrode, wherein the electrolyte membrane includes the composite solid-state electrolyte membrane provided in the first aspect of this application and / or the composite solid-state electrolyte membrane prepared by the preparation method provided in the second aspect of this application.
[0023] In some embodiments, the positive electrode comprises a positive electrode active material, a polymer solid electrolyte material, and a conductive agent, and the mass ratio of the positive electrode active material, the polymer solid electrolyte material, and the conductive agent is (50-85):(10-50):(3-20).
[0024] And / or, the negative electrode comprises a lithium metal sheet.
[0025] In the composite solid electrolyte membrane provided in the first aspect of this application, a polymer porous membrane is located inside and encapsulated within the solid electrolyte layer. This polymer porous membrane provides strong mechanical properties, thus offering excellent support for the composite solid electrolyte membrane. Meanwhile, lithium particles embedded on the surface of the solid electrolyte layer not only act as fillers to reinforce the solid electrolyte but also increase the limiting current density. Therefore, the composite solid electrolyte membrane provided in this application, when used in solid-state batteries, can effectively reduce the risk of dendrite growth in the negative electrode while improving the battery's rate performance, resulting in excellent cycle charge-discharge performance.
[0026] The preparation method provided in the second aspect of this application involves mixing and drying a polymer porous membrane, which serves as a support, with an electrolyte slurry. This allows the polymer porous membrane to be embedded and encapsulated by a solid electrolyte formed from the polymer and lithium salt, creating a wetted sandwich structure. Then, through the charge-discharge process of the battery, inactive lithium particles are embedded into the surface of the composite solid electrolyte membrane, yielding the final product. The composite solid electrolyte membrane prepared in this way, when used in solid-state batteries, can effectively reduce the risk of dendrite growth on the negative electrode, while simultaneously improving the battery's rate performance and giving the battery excellent cycle charge-discharge performance.
[0027] The solid-state lithium metal battery provided in the third aspect of this application uses a composite solid-state electrolyte membrane unique to this application. Therefore, based on the characteristics of the composite solid-state electrolyte membrane, the solid-state lithium metal battery of this application not only has good safety performance but also good rate capability during cycle use, under the premise of high energy density. Attached Figure Description
[0028] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0029] Figure 1 SEM image of the PEO-LiTFSI-PE-Li composite solid electrolyte membrane prepared in Example 1;
[0030] Figure 2 SEM image of the PEO-LiTFSI solid electrolyte membrane prepared in Comparative Example 1;
[0031] Figure 3 SEM image of the PEO-LiTFSI-PE composite solid electrolyte membrane prepared in Comparative Example 2;
[0032] Figure 4 The limiting current density test results are for the PEO-LiTFSI-PE-Li composite solid electrolyte membrane prepared in Example 1;
[0033] Figure 5 The limiting current density test results are for the PEO-LiTFSI solid electrolyte membrane prepared in Comparative Example 1.
[0034] Figure 6 The limiting current density test results are for the PEO-LiTFSI-PE composite solid electrolyte membrane prepared in Comparative Example 2.
[0035] Figure 7The rate performance test results are for the all-solid-state lithium metal battery prepared in Example 2;
[0036] Figure 8 The rate performance test results are for the all-solid-state lithium metal battery prepared in Comparative Example 4.
[0037] Figure 9 The graph shows the charge-discharge curves at different rates of the all-solid-state lithium metal battery prepared in Example 2.
[0038] Figure 10 The charge-discharge curves of the all-solid-state lithium metal battery prepared in Comparative Example 4 at different rates are shown.
[0039] Figure 11 The results are the cycle performance test results of the all-solid-state lithium metal batteries in Example 2 and Comparative Example 4;
[0040] Figure 12 The charge-discharge curves of the all-solid-state lithium metal battery prepared for Comparative Example 3 are shown. Detailed Implementation
[0041] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0042] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0043] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of a single item or a plurality of items.
[0044] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.
[0045] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.
[0046] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass described in the embodiments of this application can be a mass unit known in the chemical industry, such as μg, mg, g, or kg.
[0047] The terms "first" and "second" are used for descriptive purposes only, to distinguish objects, such as substances, from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. For example, without departing from the scope of the embodiments of this application, "first XX" may also be referred to as "second XX," and similarly, "second XX" may also be referred to as "first XX." Thus, features defined with "first" and "second" may explicitly or implicitly include one or more of that feature.
[0048] Currently used lithium-ion batteries cannot simultaneously meet the requirements of high safety and high energy density. Based on the advantages and disadvantages of solid-state metal batteries, developing a polymer solid electrolyte with low thickness and the ability to withstand high limiting current density is particularly important for promoting the development of solid-state lithium metal batteries.
[0049] Based on this, this application presents a composite solid electrolyte membrane, in which a polymer porous membrane is used as a support, and a polymer solid electrolyte is coated onto the polymer porous membrane to form a wetted sandwich structure. Simultaneously, lithium particles are embedded as fillers into the solid electrolyte layer to form a filler-reinforced solid electrolyte. By comprehensively utilizing the properties of the polymer porous membrane and lithium particles, the composite solid electrolyte membrane can still improve the cycle charge-discharge performance of solid lithium metal batteries even with a relatively thin membrane. The specific technical solution is as follows.
[0050] The first aspect of this application provides a composite solid electrolyte membrane. Specifically, the composite solid electrolyte membrane of this application includes a polymer porous membrane and a solid electrolyte layer. The polymer porous membrane is a porous membrane material formed from a polymer, and the solid electrolyte layer covers the polymer porous membrane and is partially embedded in the internal pores of the polymer porous membrane; that is, the polymer electrolyte material of the solid electrolyte layer covers the surface of the polymer porous membrane, and a portion of the polymer electrolyte material is embedded in the pores inside the polymer porous membrane. The solid electrolyte layer includes two opposing surfaces, at least one surface of which lithium particles are embedded.
[0051] In the composite solid electrolyte membrane of this application embodiment, a polymer porous membrane is located inside and encapsulated by the solid electrolyte layer. The polymer porous membrane provides strong mechanical properties, thus playing a good supporting role for the composite solid electrolyte membrane. The lithium particles embedded on the surface of the solid electrolyte layer not only serve as fillers to reinforce the solid electrolyte but also increase the limiting current density. Therefore, the composite solid electrolyte membrane provided in this application embodiment can effectively reduce the risk of negative electrode dendrite growth in solid-state batteries, while improving battery rate performance and giving the battery excellent charge-discharge cycle performance.
[0052] In some embodiments, the lithium metal particles include lithium metal fillers embedded through battery electrochemical deposition-stripping; specifically, this can be an inactive lithium material generated and filled in the solid electrolyte layer during the charge-discharge process of assembling a composite solid electrolyte membrane and lithium metal into a battery. The polymer porous membrane, as a substrate, provides strong mechanical properties, while the in-situ generated inactive lithium, as a filler, further improves the limiting current density, effectively reduces the risk of lithium dendrite growth, and enhances safety and rate performance.
[0053] In some embodiments, the lithium particles have a particle size of 50 nm to 10 μm. Exemplarily, the size of these lithium particles can be values such as 50 nm, 80 nm, 100 nm, 200 nm, 500 nm, 800 nm, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, etc.
[0054] In some embodiments, the polymer solid electrolyte is composed of a polymer and a lithium salt. The polymer may be selected from at least one of polyethylene oxide (PEO), polyacrylonitrile (PAN), and polyvinylidene fluoride (PVDF), while the lithium salt may be selected from at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), LLTO (lithium lanthanum titanium oxide), LLZO (lithium lanthanum zirconium oxide), and LATP (lithium aluminum titanium phosphate). For example, it may be a PEO-based solid electrolyte.
[0055] In some embodiments, the polymer in the polymer solid electrolyte is selected from polyethylene oxide, the lithium salt is selected from lithium bis(trifluoromethanesulfonyl)imide, and the molar ratio of polymer to lithium salt is (14-24):1. Exemplarily, the molar ratio of polymer to lithium salt can be 14:1, 18:1, 20:1, 22:1, 24:1, etc.
[0056] In some embodiments, the polymer porous membrane is selected from at least one of polyethylene (PE) porous membrane, polypropylene (PP) porous membrane, polyimide (PI) porous membrane, and polyacrylonitrile (PAN) porous membrane. Further, the thickness of the above-mentioned polymer porous membrane is in the range of 2–10 μm; the pore size is in the range of 20–300 nm; and the porosity is in the range of 30–70%. By selecting the thickness, pore size, and porosity of the polymer porous membrane, it can provide excellent support while also facilitating ion transport.
[0057] In some embodiments, the thickness of the composite solid electrolyte membrane is less than 20 μm, meaning that the overall thickness of the composite solid electrolyte membrane formed by the solid electrolyte layer coating the polymer porous membrane and partially embedding it in the internal pores of the polymer porous membrane is less than 20 μm. Such a composite solid electrolyte membrane, used in solid-state lithium metal batteries, exhibits a high limiting current density under ultra-thin conditions, resulting in excellent energy density and good cycle charge-discharge performance.
[0058] Secondly, embodiments of this application provide a method for preparing a composite solid electrolyte membrane. Specifically, the preparation method of this application includes the following steps:
[0059] S01: Formulate electrolyte slurry containing polymer and lithium salt;
[0060] S02: After combining the electrolyte slurry and the polymer porous membrane, the mixture is dried to obtain the initial composite solid electrolyte membrane;
[0061] S03: Assemble the initial composite solid electrolyte membrane with lithium metal into a battery, and then perform charge and discharge treatment to embed inactive lithium on the surface of the initial composite solid electrolyte membrane, thus obtaining a composite solid electrolyte membrane.
[0062] In this embodiment, a polymer porous membrane serving as a support is mixed and dried with an electrolyte slurry. The polymer porous membrane is then embedded and encapsulated by a solid electrolyte formed from the polymer and lithium salt, creating a wetted sandwich structure. Inactive lithium particles are then embedded into the surface of the composite solid electrolyte membrane during the battery's charge-discharge process, resulting in the final composite solid electrolyte membrane product. The composite solid electrolyte membrane prepared in this embodiment can effectively reduce the risk of dendrite growth on the negative electrode when used in solid-state batteries, while simultaneously improving the battery's rate performance and giving the battery excellent cycle charge-discharge performance.
[0063] Specifically, the inactive lithium in the embodiments of this application is what is commonly referred to in the art as dead lithium, which refers to inactive lithium formed during the cycling process of a lithium metal battery due to the disconnection of lithium from the electrochemical circuit. It mainly consists of two parts: one is the lithium-containing compound in the solid electrolyte interphase (SEI), and the other is the metallic lithium encapsulated by the SEI.
[0064] In some embodiments, in the electrolyte slurry of step S01, the polymer may be selected from at least one of polyethylene oxide (PEO), polyacrylonitrile (PAN), and polyvinylidene fluoride (PVDF), while the lithium salt may be selected from at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), LLTO (lithium lanthanum titanium oxide), LLZO (lithium lanthanum zirconium oxide), and LATP (lithium aluminum titanium phosphate). For example, it may be PEO and lithium salt. Specifically, the polymer and lithium salt raw materials may be weighed and then dissolved in a solvent such as acetonitrile (ACN) to form an electrolyte solution slurry.
[0065] In some embodiments, the molar ratio of polymer to lithium salt in the electrolyte slurry is (14–24):1. Further, the total mass concentration of polymer and lithium salt is 0.01–0.1 g·L⁻¹. -1 (g / mL); the electrolyte slurry is evenly dispersed within this concentration range.
[0066] In some embodiments, the step of combining the electrolyte slurry and the polymer porous membrane in step S02 includes: coating the electrolyte slurry on both surfaces of the polymer porous membrane, or placing the polymer porous membrane in the electrolyte slurry and letting it stand for 4 to 6 hours.
[0067] For example, a certain amount of electrolyte slurry can be coated on both sides of a polymer porous membrane, and then placed in a glove box under an argon atmosphere (the placement time can be 30-50 hours) to evaporate the solvent, thereby obtaining an initial composite solid electrolyte membrane with a thickness of less than 20 μm. Alternatively, the polymer porous membrane can be placed in an electrolyte slurry and allowed to stand for 4-6 hours, then removed and placed on a polytetrafluoroethylene (PTFE) plate to dry (the drying time can be 30-50 hours), and then peeled off to obtain an initial composite solid electrolyte membrane with a thickness of less than 20 μm.
[0068] In some embodiments, assembling the initial composite solid electrolyte membrane with lithium metal into a battery in step S03 can be either a half-cell or a full-cell battery.
[0069] In some embodiments, the process of charging and discharging a half-cell or a full-cell battery includes: using a constant current of 0.3-0.7 mA / cm². 2 The current density is used for charge-discharge cycles, and the cycle time can be 20–200 hours. Each charge cycle can be 2–8 minutes, and each discharge cycle can be 2–8 minutes. By cycling for 20–200 hours, dead lithium (i.e., inactive lithium filler) can be embedded into the surface of the initial composite solid electrolyte membrane, thus obtaining the final composite solid electrolyte membrane product.
[0070] Thirdly, embodiments of this application provide a solid-state lithium metal battery. Specifically, the solid-state lithium metal battery of this application includes a positive electrode, a negative electrode, and an electrolyte membrane located between the positive and negative electrodes. The electrolyte membrane includes the composite solid-state electrolyte membrane provided in the first aspect of this application and / or the composite solid-state electrolyte membrane prepared by the preparation method provided in the second aspect of this application.
[0071] Based on the characteristics of the composite solid electrolyte membrane, the solid lithium metal battery of this application embodiment not only has good safety performance during cycle use, but also has good rate capability, under the premise of high energy density.
[0072] In some embodiments, the positive electrode comprises a positive electrode active material, a polymer solid electrolyte material, and a conductive agent, wherein the mass ratio of the positive electrode active material, the polymer solid electrolyte material, and the conductive agent is (50–85):(10–50):(3–20). Specifically, based on 100% of the total weight of the above materials, the positive electrode active material may be selected from one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and lithium nickel cobalt manganese oxide, accounting for 50%–85% of the total weight; the polymer solid electrolyte material may be the same as the polymer solid electrolyte material in the composite solid electrolyte membrane, for example, it may be PEO-LiTFSI, accounting for 10%–50% of the total weight; and the conductive agent accounts for 3%–20% of the total weight of the positive electrode, and the conductive agent may be selected from one or more of carbon nanotubes, carbon nanofibers, graphene, Super P, Ketjen Black, acetylene black, and activated carbon.
[0073] In some embodiments, the negative electrode comprises a lithium metal sheet.
[0074] The composite solid electrolyte membrane used in the solid-state lithium metal battery of this application embodiment utilizes the supporting effect of a polymer porous membrane. A polymer solid electrolyte is cast onto the polymer porous membrane to form an impregnated sandwich structure. Simultaneously, lithium particles reinforce the solid electrolyte and increase the limiting current density. This allows the solid-state lithium metal battery to exhibit not only excellent safety performance during cycle use, but also excellent rate capability, all while maintaining high energy density.
[0075] In some embodiments, lithium particles generated in situ by constant current deposition-stripping are smaller dead lithium fillers, and the presence of a polymer porous membrane reduces the contact between the dead lithium filler and the electrode, thereby significantly improving the limiting current density of the composite solid electrolyte membrane and reducing the risk of short circuits in solid lithium metal batteries due to lithium dendrite growth.
[0076] The following description is based on specific embodiments. It should be noted that the following embodiments are for further illustration only and do not limit the scope of protection of the implementation methods of this application to the following scenarios. The raw materials and equipment used in the embodiments of this application were all obtained by purchasing commercially available products.
[0077] Example 1
[0078] A composite solid electrolyte membrane (represented by PEO-LiTFSI-PE-Li) includes: a polymer porous membrane and a solid electrolyte layer, wherein the solid electrolyte layer covers the polymer porous membrane and is partially embedded in the internal pores of the polymer porous membrane; wherein the polymer porous membrane is a PE porous membrane, the polymer solid electrolyte of the solid electrolyte layer is PEO-LiTFSI, and lithium particles are embedded on the surface of the solid electrolyte layer.
[0079] The preparation method of the above-mentioned composite solid electrolyte membrane includes the following steps:
[0080] (1) Preparation of PEO-LiTFSI solution: Weigh 0.754g PEO and 0.246g LiTFSI in an Ar glove box and place them in a 20mL glass bottle. Add solvent ACN to make the total volume of the solution 20mL. Add a stir bar and stir overnight until the solution is transparent to obtain PEO-LiTFSI solution.
[0081] (2) Preparation of PEO-LiTFSI-PE composite solid electrolyte membrane: The PE porous membrane (thickness 7μm, porosity 40%, pore size about 200nm) was cut into circles with a diameter of 19mm and immersed in PEO-LiTFSI solution for 5h. Then, the PE porous membrane was lifted and placed on a PTFE plate to dry for 48 hours before being peeled off to obtain the PEO-LiTFSI-PE solid electrolyte membrane.
[0082] (3) Preparation of PEO-LiTFSI-PE-Li composite solid electrolyte membrane: The PEO-LiTFSI-PE solid electrolyte membrane obtained in step (2) above and two lithium metal sheets with a diameter of 12 mm were used to form a symmetrical battery, and the symmetrical battery was placed at 60°C for 10 h. The constant current charge-discharge current density was set to 0.7 mAh·cm³. -2 The charge and discharge times are 5 minutes each, and constant current charge and discharge is performed for 100 hours to activate and generate dead lithium filler. The dead lithium filler is then embedded into the PEO-LiTFSI solid electrolyte on the surface. After activation, a PEO-LiTFSI-PE-Li composite solid electrolyte membrane is obtained.
[0083] Characterization and Testing: (a) Sample Morphology Characterization: The symmetrical cell described above was disassembled, and the PEO-LiTFSI-PE-Li composite solid electrolyte membrane was removed. The surface morphology of the PEO-LiTFSI-PE-Li composite solid electrolyte membrane was characterized by scanning electron microscopy. (b) Limiting Current Density Test: The symmetrical cell after activation in step (3) was subjected to a limiting current density test. The charge and discharge current was set from 0.5 mA·cm⁻¹. -2 Increased to 1.0 mA·cm -2 Each time, it increases by 0.5 mA·cm -2 Each current density cycle is repeated 5 times, with each cycle consisting of 30 minutes of charging and discharging.
[0084] Example 2
[0085] The specific preparation steps of an all-solid-state lithium metal battery are as follows:
[0086] (1) Preparation of positive electrode slurry: In an Ar gas glove box, weigh 700 mg of lithium iron phosphate and 100 mg of conductive carbon black and add them to a 20 mL glass bottle. Measure 4 mL of the PEO-LiTFSI solution in step (1) of Example 1 (the solid content of the corresponding PEO-LiTFSI is 200 mg), add it to the glass bottle and add a stir bar. Stir overnight for 10 h to obtain lithium iron phosphate positive electrode slurry.
[0087] (2) Preparation of positive electrode sheet: In an Ar gas glove box, the positive electrode slurry obtained in step (1) of this embodiment is coated on carbon-coated aluminum foil. After drying for 24 hours, the electrode is cut into a circular lithium iron phosphate electrode sheet with a diameter of 10 mm, which is the positive electrode sheet.
[0088] (3) Assembly of all-solid-state lithium metal battery: In an Ar gas glove box, lithium metal is used as the negative electrode, the above-mentioned lithium iron phosphate circular electrode is used as the positive electrode, and the PEO-LiTFSI-PE composite solid electrolyte membrane prepared in Example 1 is used as the solid electrolyte to assemble a coin cell.
[0089] (4) Filling with dead lithium filler: First, let the assembled coin cells stand at 60°C for 24 hours, then charge them at a rate of 0.5C for one hour. Then charge them at 0.5mA cm -2 The battery was charged and discharged at a current density of 5 min for 300 cycles. Then, it was charged at 0.5 C to 4.2 V and held at a constant voltage until the current was less than 0.05 C, thus completing the filling of dead lithium filler. At this point, the PEO-LiTFSI-PE composite solid electrolyte membrane was transformed into a PEO-LiTFSI-PE-Li composite solid electrolyte membrane, yielding the final all-solid-state lithium metal battery.
[0090] Performance testing: (a) Rate performance test: After completing step (4), charge-discharge and rate tests were performed on the all-solid-state lithium metal battery, maintaining a charging rate of 0.5C and a discharging rate of 0.5–3C. (b) Cycle performance test: After completing step (4), charge-discharge tests were performed on the all-solid-state lithium metal battery. The charging process was constant current and constant voltage charging, with a charging rate of 0.5–1C. After charging to 4.2V, the voltage was kept constant until the current was less than 0.05C. The discharging process was constant current discharging, with a discharging rate of 0.5–3C.
[0091] Comparative Example 1
[0092] A solid electrolyte membrane (represented by PEO-LiTFSI) is composed of the polymer solid electrolyte PEO-LiTFSI.
[0093] The preparation steps of the above solid electrolyte membrane include: in an Ar gas glove box, the PEO-LiTFSI solution in step (1) of Example 1 is drawn with a dropper and dropped into a PTFE groove with a diameter of 19 mm and a depth of 2 mm. After the solution dries in the glove box, the PEO-LiTFSI solid electrolyte membrane is obtained and its thickness is controlled to be 100 μm.
[0094] Characterization and Testing: (a) Sample Morphology Characterization: The surface morphology of the PEO-LiTFSI solid electrolyte membrane was characterized by scanning electron microscopy. (b) Limiting Current Density Test: The PEO-LiTFSI solid electrolyte membrane and lithium metal were assembled into a coin cell, and the cell was placed at 60°C for 10 hours. The charge and discharge current was set from 0.5 mA·cm⁻¹. -2 Increased to 1.0 mA·cm -2 Each time, it increases by 0.5 mA·cm -2 Each current density cycle is repeated 5 times, with each cycle consisting of 30 minutes of charging and discharging.
[0095] Comparative Example 2
[0096] A composite solid electrolyte membrane (represented by PEO-LiTFSI-PE) includes: a polymer porous membrane and a solid electrolyte layer, wherein the solid electrolyte layer covers the polymer porous membrane and is partially embedded in the internal pores of the polymer porous membrane; wherein the polymer porous membrane is a PE porous membrane, and the polymer solid electrolyte of the solid electrolyte layer is PEO-LiTFSI.
[0097] The preparation method of PEO-LiTFSI-PE composite solid electrolyte membrane is as follows:
[0098] (1) Preparation of PEO-LiTFSI solution: Weigh 0.754g PEO and 0.246g LiTFSI in an Ar glove box and place them in a 20mL glass bottle. Add solvent ACN to make the total volume of the solution 20mL. Add a stir bar and stir overnight until the solution is transparent to obtain PEO-LiTFSI solution.
[0099] (2) Preparation of PEO-LiTFSI-PE composite solid electrolyte membrane: The PE porous membrane (thickness 7μm, porosity 40%, pore size about 200nm) was cut into circles with a diameter of 19mm and immersed in PEO-LiTFSI solution for 5h. Then, the PE porous membrane was lifted and placed on a PTFE plate to dry for 48 hours before being peeled off to obtain the PEO-LiTFSI-PE solid electrolyte membrane.
[0100] Characterization and Testing: (a) Sample Morphology Characterization: The surface morphology of the PEO-LiTFSI-PE composite solid electrolyte membrane was characterized by scanning electron microscopy. (b) Limiting Current Density Test: The PEO-LiTFSI-PE composite solid electrolyte membrane and lithium metal were assembled into a coin cell, and the cell was placed at 60°C for 10 hours. The charge and discharge current was set from 0.5 mA·cm⁻¹. -2 Increased to 1.0 mA·cm -2 Each time, it increases by 0.5 mA·cm -2 Each current density cycle is repeated 5 times, with each cycle consisting of 30 minutes of charging and discharging.
[0101] Comparative Example 3
[0102] The specific preparation steps of an all-solid-state lithium metal battery are as follows:
[0103] Lithium metal battery assembly: In an Ar gas glove box, lithium metal is used as the negative electrode, lithium iron phosphate circular electrode is used as the positive electrode, and PEO-LiTFSI solid electrolyte membrane is used as the solid electrolyte to assemble coin cells.
[0104] Performance testing: First, the battery was left to stand for 24 hours, then charge and discharge tests were performed. The charging process was constant current and constant voltage charging, with a charging rate of 0.5–1C. After charging to 4.2V, the voltage was kept constant until the current was less than 0.05C. The discharging process was constant current discharging, with a discharging rate of 0.5–3C.
[0105] Comparative Example 4
[0106] The specific preparation steps of an all-solid-state lithium metal battery are as follows:
[0107] Lithium metal battery assembly: In an Ar gas glove box, lithium metal is used as the negative electrode, lithium iron phosphate circular electrode is used as the positive electrode, and PEO-LiTFSI-PE composite solid electrolyte membrane is used as the solid electrolyte to assemble coin cells.
[0108] Performance testing: First, the battery was left to stand for 24 hours, then charge and discharge tests were performed. The charging process was constant current and constant voltage charging, with a charging rate of 0.5–1C. After charging to 4.2V, the voltage was kept constant until the current was less than 0.05C. The discharging process was constant current discharging, with a discharging rate of 0.5–3C.
[0109] Analysis of Experimental Results
[0110] Morphology analysis: SEM image of the PEO-LiTFSI-PE-Li composite solid electrolyte membrane in Example 1 is shown below. Figure 1 As shown, the SEM image of the PEO-LiTFSI solid electrolyte membrane in Comparative Example 1 is as follows. Figure 2 As shown, the SEMT diagram of the PEO-LiTFSI-PE composite solid electrolyte membrane in Comparative Example 2 is as follows. Figure 3 As shown in the figure, the results indicate that spherical PEO particles with a diameter of approximately 100 micrometers are clearly visible on the surface of the PEO-LiTFSI solid electrolyte membrane. The PEO-LiTFSI-PE composite solid electrolyte membrane has irregular particles with a diameter of approximately 40 micrometers on its surface. The PEO-LiTFSI-PE-Li composite solid electrolyte membrane, on the other hand, has uniformly distributed solid particle fillers with a particle size ranging from 50 nm to 10 μm on its surface. These particle fillers are dead lithium fillers generated during the constant current charge-discharge activation process. The presence of these fillers helps to accelerate lithium-ion conduction and extend the lithium growth path, thereby increasing the limiting current density of the solid electrolyte.
[0111] Limiting current density results: The limiting current density test results of the PEO-LiTFSI-PE-Li composite solid electrolyte membrane in Example 1 are as follows: Figure 4 As shown, the limiting current density test results of the PEO-LiTFSI solid electrolyte membrane in Comparative Example 1 are as follows: Figure 5 As shown, the limiting current density test results of the PEO-LiTFSI-PE composite solid electrolyte membrane in Comparative Example 2 are as follows: Figure 6 As shown in the figure, the results indicate that the overpotential gradually increases with increasing current density. When the current density increases to 0.20 mA·cm⁻¹, the overpotential increases further. -2 At that time, none of the half-cells corresponding to the three solid electrolytes experienced short circuits. When the current density increased to 0.25 mA·cm⁻¹... -2Subsequently, the battery corresponding to the PEO-LiTFSI solid electrolyte membrane began to exhibit short-circuit phenomena, indicating that lithium dendrites had begun to grow and penetrated the solid electrolyte, causing the short circuit. The limiting current density that the PEO-LiTFSI solid electrolyte membrane can withstand is 0.25 mA·cm⁻¹. -2 As the current density continues to increase, when the current density increases to 0.35 mA·cm -2 At this point, the battery corresponding to the PEO-LiTFSI-PE composite solid electrolyte membrane began to exhibit micro-short circuits, indicating that lithium dendrites began to grow and penetrated the solid electrolyte, causing a short circuit. The limiting current density that this sample could withstand was 0.35 mA·cm⁻¹. -2 When the current density increases to 1.0 mA·cm -2 At that time, the battery corresponding to the PEO-LiTFSI-PE-Li composite solid electrolyte membrane did not experience a short circuit, meaning that the limiting current density that the sample in Example 1 could withstand was at least 1.0 mA·cm⁻¹. -2 .
[0112] Rate performance test results: Rate performance tests were conducted on the all-solid-state lithium metal batteries in Example 2 and Comparative Example 4, and the results are as follows: Figures 7-10 As shown in the figure, when the discharge rate is 0.5C, the specific capacities of Example 2 and Comparative Example 4 are 159 mAh·g. -1 and 160mAh·g -1 The specific capacities of both examples are comparable. However, when the discharge rate increases to 3C, the specific capacities of Example 2 and Comparative Example 4 are 145 mAh·g, respectively. -1 and 122mAh·g -1 The specific capacity retention rate of Example 2 was 91.2%, while that of Comparative Example 4 was 76.25%. Furthermore, the charge-discharge curves of both examples show that Example 2 has a lower polarization voltage. Therefore, the all-solid-state lithium metal battery corresponding to the PEO-LiTFSI-PE-Li composite solid electrolyte membrane exhibits better rate performance, and the PEO-LiTFSI-PE-Li composite solid electrolyte membrane is superior to the PEO-LiTFSI-PE composite solid electrolyte membrane.
[0113] Cyclic performance test results: Cyclic performance tests were conducted on the all-solid-state lithium metal batteries in Example 2, Comparative Example 3, and Comparative Example 4, and the results are as follows: Figure 11 , Figure 12As shown in the figure, Example 2 exhibits a higher specific capacity and better cycle stability than Comparative Example 4. Comparative Example 3, however, experienced a short circuit during the initial charging process. This indicates that the all-solid-state lithium metal battery corresponding to the PEO-LiTFSI-PE-Li composite solid-state electrolyte demonstrates better cycle performance, and the PEO-LiTFSI-PE-Li composite solid-state electrolyte membrane is superior to both the PEO-LiTFSI-PE composite solid-state electrolyte membrane and the PEO-LiTFSI solid-state electrolyte membrane.
[0114] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A composite solid electrolyte membrane, characterized in that, include: A polymer porous membrane and a solid electrolyte layer, wherein the solid electrolyte layer covers the polymer porous membrane and is partially embedded in the internal pores of the polymer porous membrane, and the material of the solid electrolyte layer includes a polymer solid electrolyte; the solid electrolyte layer includes two surfaces disposed opposite to each other, and at least one surface has lithium particles embedded therein.
2. The composite solid electrolyte membrane as described in claim 1, characterized in that, The lithium particles include non-active lithium fillers embedded via battery electrochemical deposition-stripping. And / or, the lithium particles have a particle size of 50 nm to 10 μm.
3. The composite solid electrolyte membrane as described in claim 1, characterized in that, The polymer solid electrolyte is composed of a polymer and a lithium salt, wherein the polymer is selected from at least one of polyethylene oxide, polyacrylonitrile, and polyvinylidene fluoride, and the lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, and lithium aluminum titanium phosphate.
4. The composite solid electrolyte membrane as described in claim 3, characterized in that, The polymer is selected from polyethylene oxide, the lithium salt is selected from lithium bis(trifluoromethanesulfonyl)imide, and the molar ratio of the polymer to the lithium salt is (14-24):
1.
5. The composite solid electrolyte membrane according to any one of claims 1-4, characterized in that, The polymer porous membrane is selected from at least one of polyethylene porous membrane, polypropylene porous membrane, polyimide porous membrane, and polyacrylonitrile porous membrane; And / or, the polymer porous membrane has a thickness of 2–10 μm, a pore size of 20–300 nm, and a porosity of 30–70%; And / or, the thickness of the composite solid electrolyte membrane is less than 20 μm.
6. A method for preparing a composite solid electrolyte membrane, characterized in that, Includes the following steps: Prepare an electrolyte slurry containing polymers and lithium salts; The electrolyte slurry and the polymer porous membrane are mixed and then dried to obtain an initial composite solid electrolyte membrane. The initial composite solid electrolyte membrane is assembled with lithium metal into a battery, and then charged and discharged to embed inactive lithium on the surface of the initial composite solid electrolyte membrane, thus obtaining a composite solid electrolyte membrane.
7. The preparation method according to claim 6, characterized in that, The molar ratio of the polymer to the lithium salt in the electrolyte slurry is (14–24):1, and the total mass concentration of the polymer and the lithium salt is 0.01–0.1 g·L⁻¹. -1 ; And / or, the polymer is selected from at least one of polyethylene oxide, polyacrylonitrile, and polyvinylidene fluoride, and the lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, and lithium aluminum titanium phosphate.
8. The preparation method according to claim 6 or 7, characterized in that, The step of mixing the electrolyte slurry and the polymer porous membrane includes: coating the electrolyte slurry on both surfaces of the polymer porous membrane, or placing the polymer porous membrane in the electrolyte slurry and letting it stand for 4 to 6 hours; And / or, the conditions for the charge-discharge treatment include: 0.2–0.7 mA·cm⁻¹ -2 Under constant current density conditions, charge and discharge cycles were performed for 20–200 hours.
9. A solid-state lithium metal battery, comprising a positive electrode, a negative electrode, and an electrolyte membrane located between the positive electrode and the negative electrode, characterized in that, The electrolyte membrane includes the composite solid electrolyte membrane according to any one of claims 1 to 5 and / or the composite solid electrolyte membrane prepared by the preparation method according to any one of claims 6 to 8.
10. The solid-state lithium metal battery as described in claim 9, characterized in that, The positive electrode contains a positive electrode active material, a polymer solid electrolyte material, and a conductive agent, and the mass ratio of the positive electrode active material, the polymer solid electrolyte material, and the conductive agent is (50-85):(10-50):(3-20). And / or, the negative electrode comprises a lithium metal sheet.